PENGARUH LIKUIDITAS, LEVERAGE, OPERATING CAPACITY, PROFITABILITAS DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2016) - Lilik Febrina, 14.05.52.0051; Lisiantara, G. Anggana (Students' Journal of Accounting and Banking, 2018)
This study aims to examine the effect of liquidity, leverage, operating capacity, profitability, and sales growth of financial distress.  This research was conducted at the companies listed on the Stock Exchange in 2013-2016. The samples used were as many as 260 observations selected using purposive sampling method.  Data collection was done by using the documentation obtained from BEI website and Pojok BEI-Unisbank Stikubank (Unisbank). The analysis technique used is logistic regession. The results of the analysis of this study indicate that the leverage,operating capacity, and profitability  rations are able to affects the financial distress of manufacturing company, while the likuidity and sales growth ratios are not able to influence the probability of financial distress.Keywords : Liquidity, Leverage, Operating Capacity, Profitability,  Sales Growth, Financial Distress